Education Marginalization Of Bajo Children Based On Local Wisdom - Maemunah, Maemunah; Haniah, St.; Mukramin, Sam'un (CV. Inara, 2021)
Empowerment of education in a society that has limitations in all aspects, becomes a separate obstacle in efforts to eradicate the marginalization of education. This is one of the educational chaotics which is still experiencing fluctuations in the implementation of central policies which are regulated centrally and unilaterally without considering the local wisdom of each different region and resulting in a slump in the education of the Bajo Tribe children. This study uses descriptive qualitative with a case study approach of nine informants with data collection techniques of observation, interviews, and documentation and then analyzed. Strategies for alleviating the Marginalization of Education for Bajo Tribe children in North Kolaka Regency, namely: a) an effort to internalize the values ​​believed by the community itself; b) empowerment through education based on local wisdom which includes: parental awareness of education, partisanship with government policies, and utilization of the environment for education.